Предмет: Алгебра, автор: noskova765

1.упростите выражение :

а) 6·(2а-7)·(3-а) -3 (1-4а)·(4а+1)=

б) 2х·(х-3)·(х²+3х+9)-(3х²-1)²=

2.решите уравнение :

х³-х²+2х-2=0

(СРОЧНО!!!) ЗАРАНИЕ СПАСИБО

Ответы

Автор ответа: BloodyGolubka
1

Ответ: 1. а) 36a² + 78a - 129

б) -x⁴ + 6x² - 54x - 1

2. x₁ = 1   x₂ = 1

Объяснение:

1. а) 6 * (6a - 2a² - 21 + 7a) - 3 (4a + 1 - 16a² - 4a) =

= 36a - 12a² - 126 + 42a - 12a - 3 + 48a² + 12a =

= 36a² + 78a - 129

б) 2x (x³ + 3x² + 9x - 3x² - 9x - 27) - (3x⁴ - 2 * 3x² + 1) =

= 2x⁴ + 6x³ + 18x² - 6x³ - 18x² - 54x - 3x⁴ + 6x² - 1 =

=-x⁴ + 6x² - 54x - 1

2. (x³ - x²) + (2x - 2) = 0

x² (x - 1) + 2 (x - 1) = 0

(x - 1) (x² - 1) = 0

x - 1 = 0

x₁ = 1

x² - 1 = 0

x² = 1

x₂ = 1

Похожие вопросы